Avaliação da resistência à corrosão de revestimentos da liga UNS N06625 depositados pelo processo PTA-P - Santos, Ana Claudia dos (2015)
The search for versatile materials that associate high corrosion resistance and high mechanical properties in severe environments, in order to meet the more demanding operational conditions has become a challenge for the petrochemical, thermoelectric, naval and other industries. In this context, weld overlay with nickel-based alloys becomes an interesting option for construction and repair of equipments for applications in severe corrosion environments, allowing to achieve the desired characteristics with significant cost reduction. In specific applications the high overlay dilution must be controlled due to high iron content encountered. The objective of this work is to evaluate the intergranular and pitting corrosion of the alloy UNS N06625, with different dilution values, deposited through Plasma Transferred Arc with Powder (PTA-P) welding technique on an ASTM A36 carbon steel substrate. With the evaluation and characterization of the alloy UNS N06625 aimed the comprehension of the dilution effect on the coating microstructure and properties. The mechanical properties tests were analyzed through microhardness tests. The microstructural characterization consisted of analyses with the optical microscope, with the Scanning Electron Microscope (SEM) and chemical composition with the EDS module. Double-Loop Electrochemical Potentiokinetic Reactivation Test (DL-EPR) and Cyclic Potentiodynamic Polarization tests were done to evaluate intergranular and pitting corrosion resistance, respectively. With this work it was possible to observe that the dilution difference influences in a smooth way in the coating microhardness. The microstructures presented aγ matrix with secondary interdendritic phases. The coatings did not present intergranular corrosion in the test conditions and the pitting corrosion susceptibility was able to be evaluated only through the hysteresis presented in the polarization curves.